The Performative Reception of The Qur’an in Mappasuru’ Tradition: A Living Qur’an Study in Tampumia Village - Muh Alimin; M. Zuhri Abu Nawas; Hamdani Thaha; Syahruddin Syahruddin; Gita Gita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2026)
The study discusses the phenomenon of the Living Qur'an in the burial of the deceased. Using the Living Qur'an approach, which focuses on the community's understanding of the readings they often use in a practice called mappasuru, the researcher used observation and interview methods and techniques as well as documentation, namely collecting data through field observations and discussions with mappasuru practitioners. The main sources are the results of interviews and observations, supported by relevant journals that discuss the issues in general. The results of the study on the Living Qur'an phenomenon in the practice of burying the dead in Tampumia Village show that: first, the mappasuru’ procedure begins when the body is lowered into the grave until the coffin is closed. Second, the recitations used are Q.S al-Fatihah/1:1-7, QS Taha/20:55, QS al-Fajr/89:27-28. Q.S Quraisy/106:1-1 and Q.S al-Ikhlas/112:1-1. Third, this study shows a shift in the function of the Qur'an from textual-informative meaning to performative meaning. In the practice of mappasuru, the community prioritizes the sacredness and efficacy of the ritual (benefits) of the verse over the accuracy of its literal meaning. This implies that in contemporary Qur'anic studies, the authority of the text lives not only through the interpretations of scholars, but also through its functional reception within the community.